Binomial Cube

Cube Sum

A cubed binomial (sum) is equal to the cube of the first, plus three times the square of the first by the second, plus three times the first by the square of the second, plus the cube of the second.

(a + b)3 = a3 + 3 · a2 · b + 3 · a · b2 + b3

(x + 3)3 = x 3 + 3 · x2 · 3 + 3 · x · 32 + 33 =

= x 3 + 9x2 + 27x + 27


Cube Difference

A cubed binomial (difference) is equal to the cube of the first, minus three times the square of the first by the second, plus three times the first by the square of the second, minus the cube of the second.

(a − b)3 = a3 − 3 · a2 · b + 3 · a · b2 − b3

(2x − 3)3 = (2x)3 − 3 · (2x)2 ·3 + 3 · 2x· 32 − 33 =

= 8x 3 − 36 x2 + 54 x − 27


Examples

1(x + 2)3 = x3 + 3 · x2 · 2 + 3 · x · 22 + 23 =

= x3 + 6x2 + 12x + 8

2(3x − 2)3 = (3x)3 − 3 · (3x)2 · 2 + 3 · 3x · 22 − 23 =

= 27x 3 − 54x2 + 36x − 8

3(2x + 5)3 = (2x)3 + 3 · (2x)2 ·5 + 3 · 2x · 52 + 53 =

= 8x3 + 60 x2 + 150 x + 125





  • Top